Social engineering as shock absorbing mechanism against bank erosion: a study along Bhagirathi river, West Bengal, India. Issue 3 (3rd July 2021) - Islam, Aznarul; Guchhait, Sanat Kumar
ABSTRACT: The issue of bank erosion is very severe in the lower stretch of Bhagirathi River in West Bengal, India. During 1984–2012 the average annual rate of bank line shifting at the selected cross sections was computed to be oscillating around 10 m year −1 . Micro-level socio-economic survey portrayed that greater than 45 per cent farmers lost about 90 per cent landed property in some villages during 1970–2012 transforming large as well as marginal farmers into landless refugees. The immediate shock of land loss is reflected through decrease in per capita income. Head count ratio, poverty gap index, and poverty severity index showed an increase of poverty by 10–15 per cent. Inverse Herfindahl-Hirschman index depicted a gradual rise in occupational diversification during 1970–2012 (e.g. 1970:1.47, 1990:1.85 and 2012:2.66 for Rukunpur). To reduce the disaster risk of bank erosion, various structural measures (e.g. dyking with geotextile) that were undertaken proved futile subsequently. Therefore, the present enquiry attempts to propose some social engineering methods as shock absorbing mechanism against the threats of land-based agrarian economy. These are the three in situ modes of economic adjustment using local available resources (non-land-based household manufacturing, common property resource management, development of indigenous small scale and cottage industry) and one ex situ economic adjustment by developing labour migration.